Working while Black : the untold stories of student affairs practitioners - Tomlin, Antione D. (Identity & practice in higher education-student affairs., 2022)
Working While Black: The Untold Stories of Student Affairs Practitioners will examine the narratives of student affairs professionals and how they navigate their professional experiences. While student affairs can be a high pressure and high stress environment for all professionals, Black professionals are often overworked, underheard, and made to feel devalued. Therefore, it is important to consider how student affairs professionals are managing the profession, colleagues, and students while Black.I approach this book from an asset-based approach where chapter authors are approaching both the challenges and opportunities they have experienced due to being a Black while working as a student affairs practitioner. Chapter authors also provide poignant advice on how current and potential student affairs professionals can successfully navigate the field. One especially important contribution of this book is that our authors are from a variety of student affairs areas including: residence life, student engagement, career services, counseling, student conduct, athletics, student activities, diversity, equity, and inclusion, and academic advising. Additionally, chapter authors are student affairs professionals at predominantly White institutions, historically Black colleges and universities, and online universities. Given the breadth of experiences each chapter will provide poignant suggestions for student affairs practitioners across the nation as well as for institutions who are looking to better understand these experiences to better support their own employees.Popular education press and scholarly conversations have focused on the experiences of student affairs professionals (Renn & Hodges, 2007). There has also been scholarship around the Black student affairs professional experience (West, 2015; Husband. 2016). This book will add to the current press and scholarly conversations by allowing Black student affairs professionals to tell their own stories, providing additional insight into what it is like to work while Black. Institutions of higher education can learn much from the stories shared in this book that can inform the recruitment and retention of Black professionals. Thus, Working While Black: The Untold Stories of Student Affairs Practitioners is positioned to be a must read for all higher education professionals and institutions who are looking for strategies to support Black student affairs professionals.